Relationship between level of scientific creativity and scientific attitudes among prospective chemistry teachers - Wimbi Apriwanda Nursiwan; Chuzairy Hanri (International Journal of Evaluation and Research in Education (IJERE), 2023)
Scientific creativity and scientific attitude are important things that must be passed on in science learning. That is because the level of scientific creativity and scientific attitude could influence the performance in learning. As the same crucial components in learning, this research aimed to study the relationship between the level of scientific creativity and scientific attitudes. This study involved 92 prospective chemistry teachers in Pekanbaru, Indonesia who were selected using sample-simple random sampling. The data was collected through a chemistry scientific creativity test (CSCT) in form of open-ended questions, and a scientific attitude questionnaire. The data further was analyzed using SPSS 26.0 with a calculation of spearman correlation. The result showed that there was no relationship between the level of scientific creativity and scientific attitudes with Sig. 2-tailed=0.193, rs=0.137. It indicated that the level of scientific attitude was not the dominant factor that could influence the level of scientific creativity among prospective chemistry teachers in this study. Thus, this finding could be a consideration for educational stakeholders to explore the dominant factor that affected scientific creativity.